A common gas market for Visegrad Group countries - Kumor, Michał; Porada, Stanisław (Eastern Review, 2020)
The construction of the North-South Gas Corridor, regional energy integration and international cooperation in the Visegrad Group (Poland, Hungary, Czech Republic and Slovakia) can be determinants for the creation of a common gas market for four Eastern Europe countries (V4). The starting point for this work is concerned with the technical possibilities, chances, threats and necessary steps for the development of the existing infrastructure. The import capacities of countries neighbouring the V4 territory and the internal gas transmission potential inside the indicated group of countries have been presented in this paper. Special attention was paid to the international possibilities of using underground gas storage. The V4 countries, in particular, were examined due to their location between the Russian Federation and Western European gas consumers, and due to the need to ensure the security of supply, volumes and directions of import and export for each from. The bringing online of the gas connection between Norway and Poland, along with the construction of the Croatian LNG terminal, and the establishment of a common gas market for deliveries inside V4 may significantly contribute to determining a new physical direction of the gas flow in this part of Europe.